Liver‐directed gene therapy for ornithine aminotransferase deficiency. Issue 4 (17th January 2023) - Boffa, Iolanda; Polishchuk, Elena; De Stefano, Lucia; Dell'Aquila, Fabio; Nusco, Edoardo; Marrocco, Elena; Audano, Matteo; Pedretti, Silvia; Caterino, Marianna; Bellezza, Ilaria; Ruoppolo, Margherita; Mitro, Nico; et al.
Abstract: Gyrate atrophy of choroid and retina (GACR) is a chorioretinal degeneration caused by pathogenic variants in the gene encoding ornithine aminotransferase (OAT), an enzyme mainly expressed in liver. Affected patients have increased ornithine concentrations in blood and other body fluids and develop progressive constriction of vision fields leading to blindness. Current therapies are unsatisfactory and better treatments are highly needed. In two mouse models of OAT deficiency that recapitulates biochemical and retinal changes of GACR, we investigated the efficacy of an intravenously injected serotype 8 adeno‐associated (AAV8) vector expressing OAT under the control of a hepatocyte‐specific promoter. Following injections, OAT‐deficient mice showed reductions of ornithine concentrations in blood and eye cups compared with control mice injected with a vector expressing green fluorescent protein. AAV‐injected mice showed improved electroretinogram response and partial restoration of retinal structure up to one‐year post‐injection. In summary, hepatic OAT expression by AAV8 vector was effective at correction of hyperornithinemia and improved function and structure of the retina. In conclusion, this study provides proof‐of‐concept of efficacy of liver‐directed AAV‐mediated gene therapy of GACR. Synopsis: Deficiency of ornithine aminotransferase (OAT) results in increased plasma ornithine concentrations and retinal toxicity, especially in the retinal pigment epithelium (RPE). This study investigated liver‐directed gene transfer for OAT deficiency. Intravenous injections of AAV8 vector delivering OAT gene to hepatocytes reduced ornithine concentrations in plasma and eye. The treatment improved function and structure of the retina. Abstract : Deficiency of ornithine aminotransferase (OAT) in liver results in increased ornithine concentrations and retinal toxicity, especially the retinal pigment epithelium (RPE). This study investigated liver‐directed gene transfer for OAT deficiency.